Antibacterial and Photocatalytic Applications of Silver Nanoparticles Synthesized from Lacticaseibacillus rhamnosus (2024)
The biosynthesis of silver nanoparticles (AgNPs) presents an innovative and sustainable approach in nanotechnology with promising applications in fields such as medicine, food safety, and pharmacology. In this study, AgNPs were successfully synthesized using the probiotic strain Lacticaseibacillus rhamnosus (BCRC16000), addressing challenges related to stability, biocompatibility, and scalability that are common in conventional nanoparticle production methods. The formation of AgNPs was indicated by a color change from yellow to brown, and UV–visible spectrophotometry confirmed their presence with a characteristic absorption peak at 443 nm. Furthermore, Fourier transform infrared (FTIR) spectroscopy revealed the involvement of biomolecules in reducing silver ions, which suggests their role in stabilizing the nanoparticles. In addition, field emission scanning electron microscopy (FE-SEM) showed significant morphological and structural changes. At the same time, dynamic light scattering (DLS) and zeta potential analyses provided valuable insights such as average size (199.7 nm), distribution, and stability, reporting a polydispersity index of 0.239 and a surface charge of −36.3 mV. Notably, the AgNPs demonstrated strong antibacterial activity and photocatalytic efficiency, underscoring their potential for environmental and biomedical applications. Therefore, this study highlights the effectiveness of Lacticaseibacillus rhamnosus in the biosynthesis of AgNPs, offering valuable antibacterial and photocatalytic properties with significant industrial and scientific implications.